Sistem Inventaris Stok Obat Menggunakan Metode Exponential Moving Average - Sukaria, Petra Nugra; Muzakki, Mohammad Haris; Adhani, Muhammad Azmi; Kusrini, K; Agastya, I Made Artha (STIKOM Tunas Bangsa Pematangsiantar, 2024)
The management of drug inventory in hospitals is a crucial aspect that affects the quality of healthcare services and patient safety. Uncertain drug demand can lead to overstock, resulting in wastage due to expiration, or understock, endangering patient safety. This study aims to develop a drug inventory system using the Exponential Moving Average (EMA) method to forecast drug sales. Historical sales and purchase data from Betang Pambelum Hospital, Palangka Raya, were used for forecasting. The implementation of the EMA method proved to provide accurate forecasting results, with the Mean Absolute Percentage Error (MAPE) falling into good to very accurate categories. This system not only reduces the risks of drug overstock and understock but also helps hospitals in more efficient inventory management. The adoption of this system is expected to enhance the quality of healthcare services through better drug inventory management